Barriers to and Facilitators of Bedside Nursing Handover: A Systematic Review and Meta-synthesis. Issue 4 (12th October 2021) - Clari, Marco; Conti, Alessio; Chiarini, Daniela; Martin, Barbara; Dimonte, Valerio; Campagna, Sara
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Bedside nursing handover (BNH) has been recognized as a contributor to patient-centered care. However, concerns about its effectiveness suggest that contextual factors should be considered before and after BNH implementation. Purpose: This review aimed to identify, evaluate, and synthetize the qualitative literature on the barriers to and facilitators of BNH as experienced by nurses and patients. Methods: The Joanna Briggs Institute meta-aggregation method was applied. A systematic search was performed to identify qualitative studies published from inception to June 30, 2020. Two independent researchers assessed methodological quality and extracted data. Results: Twenty-four articles were included, comprising 161 findings, and 5 synthesized findings emerged with a moderate level of confidence. Conclusions: BNH ensures patient safety and increases satisfaction and recognition among patients and nurses. This evidence on the barriers to and facilitators of BNH could help health care providers who have implemented or plan to implement this practice.